2005
DOI: 10.1007/s10563-005-3330-3
|View full text |Cite
|
Sign up to set email alerts
|

Active sites of silica-based quantum photocatalysts for non-oxidative reactions

Abstract: Various photocatalytic reactions have been developed in recent years. Among them, non-oxidative reactions by silica-based quantum photocatalysts are quite unique. Pure silica materials, especially mesoporous silica evacuated at high temperature, were found to promote olefin metathesis upon photoirradiation at room temperature. A kind of surface defect on silica was generated through dehydroxylation at high temperature before the photoreaction, which can be photoexcited to form the first surface intermediate. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Then depending of the availability of inter system crossing mechanisms, the excited electron could transfer to a triplet state yielding phosphorescence, which has been detected using a photoluminescence spectroscopic method. [6] We were able to observe similar emission fine structure which consist of intensity maxima corresponding to each vibrational energy level of the bond in the photoactive site, in our case (Cr -O). Note our solid state photoluminescence studies (Figure 8).…”
Section: Mechanism/s Of Photocatalytic Activitysupporting
confidence: 68%
See 2 more Smart Citations
“…Then depending of the availability of inter system crossing mechanisms, the excited electron could transfer to a triplet state yielding phosphorescence, which has been detected using a photoluminescence spectroscopic method. [6] We were able to observe similar emission fine structure which consist of intensity maxima corresponding to each vibrational energy level of the bond in the photoactive site, in our case (Cr -O). Note our solid state photoluminescence studies (Figure 8).…”
Section: Mechanism/s Of Photocatalytic Activitysupporting
confidence: 68%
“…Thus, for our systems chromium was chosen as the doping agent for our more in-depth study of Cr-SiO 2 and mixed TiO 2 -SiO 2 samples. [5,6,7,8] Herein we report the observed UV and visible light activities of chromium ions loaded silica and titania based materials and possible mechanisms for the observed photocatalytic performances.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, they can promote even difficult reactions through the oxidative and reductive half reactions. On the other hand, highly dispersed photocatalysts are another type of the heterogeneous photocatalysts, which have been mentioned as single site photocatalysts, quantum photocatalysts or local excitation photocatalysts, with a unique structures and excitation states of the active sites [5,6]. In this type of photocatalysts, the active sites such as Ti cations are supported by insulating materials such as silica and zeolite, and the metal cation is coordinated by some oxygen anions on the surface of the support.…”
Section: Introductionmentioning
confidence: 99%
“…Since this initial study, numerous catalysts have been tested for photoactivated CO 2 3 , ZnO, and MgO and found that of these materials, only ZrO 2 and MgO exhibited photoactivity for the reduction of CO 2 to CO in a H 2 atmosphere. [ 20,21 ] Lo et al also demonstrated the photoreduction of CO 2 with H 2 over ZrO 2 in a circulating photocatalytic reactor. [ 22 ] More recently, CO 2 photoreduction to methanol in a hydrogen environment has been reported to occur over graphene oxide [ 23 ] and zinc-copper-gallium layered double hydroxide catalysts.…”
Section: Doi: 101002/advs201400001mentioning
confidence: 99%